Life Imprisonment and Harsh Sentences for Juveniles: A Critical Analysis under International Human Rights Law: Life Imprisonment and Harsh Sentences for Juveniles: A Critical Analysis under International Human Rights Law - Ayu Putri Bhayangkari; Maryano Maryano; Tubagus Achmad Doradjat (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2026)
This study critically examines the imposition of life imprisonment and harsh sentences on juveniles through the lens of international human rights law. Employing a normative-qualitative and comparative framework, the research analyzes core international instruments—including the Convention on the Rights of the Child (CRC), the International Covenant on Civil and Political Rights (ICCPR), and the Convention against Torture (CAT)—alongside relevant case law and global jurisprudential trends. The findings reveal a significant compliance gap between established international standards and domestic implementation, particularly in jurisdictions that continue to enforce juvenile life imprisonment without parole. The study argues that such sentencing practices contravene fundamental human rights principles, including the best interests of the child, and constitute cruel, inhuman, or degrading treatment under international law. Moreover, these approaches are scientifically untenable, ignoring developmental and neuroscientific evidence underscoring juveniles’ capacity for rehabilitation. In contrast, progressive reforms in Europe and Latin America reflect a growing shift toward restorative justice and child-centered penal models. By integrating normative analysis with comparative insights, this research contributes to academic and policy discourse on juvenile justice, offering actionable guidance for realigning domestic legal frameworks with international human rights obligations. It ultimately emphasizes the urgent need for states to abandon punitive sentencing in favor of rehabilitative approaches that are both rights-compliant and empirically grounded.